Refractory Heparin-Induced Thrombocytopenia With Cerebral Venous Sinus Thrombosis Treated With IVIg, Steroids, and a Combination of Anticoagulants: A Case Report - Mia Gonzales MD, MPH; Amrish Pipalia MD; Andrew Weil MD (SAGE Publishing, 2019)
Heparin-induced thrombocytopenia (HIT) type II is caused by antibody production that bind complexes between heparin and platelet factor 4 leading to platelet consumption and thrombosis. In a small subset of cases referred to as autoimmune HIT, the antibodies activate platelets even in the absence of heparin. Refractory HIT is a type of autoimmune HIT in which thrombocytopenia persists for weeks after heparin discontinuation and carries increased risk for thrombosis and more severe thrombocytopenia. We present a case of refractory HIT with cerebral venous sinus thrombosis (CVST) that was successfully treated with a change in anticoagulant alongside steroids and a second trial of intravenous immunoglobulin (IVIg).